ROLE OF THE PUBLIC PROSECUTOR IN RETURNING ASSETS RESULTING FROM MONEY LAUNDERING IN CORRUPTION CASES - A. Dyah Ayu Tiara; Hambali Thalib; Said Sampara (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal